Double Crop Soybean After Wheat - D. S. Hansel; J. Kimball; D. E. Shoup; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2017)
Two double crop (DC) soybean studies were conducted at Ottawa, KS, during the 2016 growing season. Soybean cultivar Asgrow 4232 (MG 4.2) was planted immediately after two different wheat harvest timings (Study 1: early-wheat harvest 18-20% seed moisture content, and Study 2: conventional-harvest, 13-14% seed moisture content). Seven treatments were evaluated in each of the soybean planting dates: 1) common practice, 2) no seed treatment (without seed fungicide + insecticide treatment), 3) non-stay green (without foliar fungicide + insecticide application), 4) high seeding rate (180,000 seeds per acre), 5) wide rows (30-inch row spacing), 6) nitrogen (N) fixation (without late fertilizer N application), and 7) kitchen sink (includes all management practices). Aboveground biomass, seed harvest index (HI) and yield were evaluated. For the early-planted study, a trade-off was documented between biomass and seed HI, presenting maximum yield also for values with lower HIs. Yield was greatest when planting in wide rows (64.5 bu/a) for the late-planted timing, and for the Nfixation treatment (64.0 bu/a) for the early-planted study. For the early-planted, yield gap (calculated as maximum minus minimum yield) was 6 bu/a, while for late-planted, yield gap was 7.5 bu/a. Best management practices for DC soybean can improve overall productivity via increasing yield with modifications in biomass and HI, and overall yield efficiency. Further testing on the effect of multiple management practices on DC soybean will be performed during the upcoming growing season.
Keywords: soybean; improve yield; intensive management